Gerechter Ausgleich und angemessene Vergütung Dispositionsmöglichkeiten bei Vergütungsansprüchen aus gesetzlichen Lizenzen - Pflüger, Claudius (Abhandlungen zum Urheber- und Kommunikationsrecht, 2017)
"The thesis examines the international and European regulations of the exceptions and limitations of copyright law and points out the leeway member states have for implementing them. The thesis analyzes solely the legal consequences of these exceptions and limitations in regard to contractual agreements. It outlines the structural concepts in InfoSocRL, UrhG, German civil law, and the law of collecting societies, and takes into account constitutional rights (GG, GRCh). The thesis also deals with the current discussion on the participation of publishers in these remuneration rights of authors. The work is aimed at authors, publishers, and collecting societies."